Microstructural transition of nanoparticle deposits from multiple dendrites to compact layer. (January 2022) - Kim, Jeonggeon; Shin, Juhwan; Lee, Donggeun
Abstract: Nanoparticle deposit has various microstructures from multiple dendrites to mesoporous compact structures depending on deposition conditions, and the required microstructures are different depending on its applications. There have been recent reports that the overall porosity of deposit can be predicted by a function of diffusive Knudsen number ( K n D ) and dimensionless translational energy ( χ F ) of the particle. Unlike compact structures, however, dendritic structures consisting of multiple dendrites cannot be characterized solely by overall porosity and their formation mechanism is not known. In this study, various structures of deposit were produced in a wide range of deposition conditions ( K n D : 10 −1.5 –10 1.5 ; χ F : 10 −3 –10 3 ) using off-lattice Monte Carlo simulation, and the unique characteristics of the deposit could be visualized by presenting local fractional accumulations of pores as color-filled contours. Furthermore, a spatial autocorrelation was calculated for the contour plot in order to find a quantitative footprint of structural features of nanoparticle deposits, in compact vs dendritic structures. As a result, we successfully identified the dendritic-to-compact structural transition in a quantitative manner, for the first time. Lastly considering the deposition behavior of particles, we developed a new model capable of a priori prediction of the specific deposit structure among compact, dendritic, and transition structures, given the deposition condition in terms of K n D and χ F . Graphical abstract: Image 1 Highlights: Various deposit structures were produced using off-lattice Monte Carlo simulation. With local porosity distribution, the structural characteristics were visualized. The compact-to-dendritic transition was quantified using spatial autocorrelation. A new model was developed to predict the microstructure of deposits.